Phytocenological characteristic of Artemisia aralensis Krash. communities in the North Aral Sea region (Experimental biology, 2018)
The article presents theresults of study of Artemisia aralensis Krasch. plant communities in the territory of the botanical station "Tereskent" and the adjacent area in the Northern Aral Sea region (Shalkar district of Aktobe region) in 2015-2016.Artemisia aralensis Krasch. is an endemic species of Kazakhstan. It was first described by I. Krasheninnikov on collections of L. Bubyr in 1908, in gravelly-clayey hills near the railway station Kara-Chokat (Aktobe region, Shalkar district). Exicat (a herbarium specimen) of Artemisia aralensis is stored in the Herbarium of the Institute of Botany and Phytointroduction of the MES RK (AA). The plant has a clear lemon scent. The life form is a semi-shrub of 30-50 cm high. Its stems are strongly and highly arboreal, covered with reddish-brown bark, they form a small turf. Root is woody, thick. It grows in a desert zone on clayey and sandy loam solonetzic soils, in dry riverbeds of temporary watercourses and on the variegated outcrops. This species is one of the natural forage resources of the pastures of the Northern Aral Sea, and the composition of its essential oils has great practical importance in medicine.As a result of the studies, six communities with the dominant role of Artemisia aralensis were described. It was determined that there are 57 species of vascular plants in composition of investigated plant communities: herbaceous perennial and annual species prevail. Poa bulbosa is a typical species in Artemisia aralensis communities. The study of the aral-sagebrush communities confirmed that the species is confined to the dry beds of temporary watercourses and erosion forms of relief. The assumption is made that the area of dominance of the species is confined to the Northern Aral region.
Keywords: Artemisia aralensis, species composition, endemic, the North Aral Sea region, plant community.